2018
DOI: 10.1210/js.2018-00259
|View full text |Cite
|
Sign up to set email alerts
|

Thyroidectomy for Amiodarone-Induced Thyrotoxicosis: Mayo Clinic Experience

Abstract: ContextAmiodarone-induced thyrotoxicosis (AIT) is a difficult diagnostic and management challenge, especially during severe thyrotoxicosis accompanied by cardiovascular compromise.ObjectiveTo evaluate thyroidectomy for the management of AIT.DesignRetrospective cohort study of adults with noncongenital heart disease with AIT after >3 months of amiodarone who underwent thyroidectomy from 1 November 2002 to 31 December 2016.SettingReferral center.PatientsThe group was comprised of 17 patients.Main Outcome Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 21 publications
2
26
0
4
Order By: Relevance
“…[61][62][63] Thyroidectomy remains a valuable option for AIT management, particularly for patients with suboptimal response to medical therapy and high risk for cardiac complications. 67 A higher prevalence of overt hypothyroidism (22.7%) as compared to controls (4.1%, p: 0.02) was found in TM patients 3 months after starting amiodarone, while the prevalence of subclinical hypothyroidism was similar in amiodarone-treated (18.2%) and untreated (15%) TM patients. 63 Overt hypothyroidism resolved spontaneously after amiodarone withdrawal in one case, while the remaining TM patients were maintained euthyroid on amiodarone by L-thyroxine administration.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…[61][62][63] Thyroidectomy remains a valuable option for AIT management, particularly for patients with suboptimal response to medical therapy and high risk for cardiac complications. 67 A higher prevalence of overt hypothyroidism (22.7%) as compared to controls (4.1%, p: 0.02) was found in TM patients 3 months after starting amiodarone, while the prevalence of subclinical hypothyroidism was similar in amiodarone-treated (18.2%) and untreated (15%) TM patients. 63 Overt hypothyroidism resolved spontaneously after amiodarone withdrawal in one case, while the remaining TM patients were maintained euthyroid on amiodarone by L-thyroxine administration.…”
mentioning
confidence: 80%
“…68 In conclusion, clinicians should keep in mind the possibility of development of thyroid disorders in patients on treatment with amiodarone even after several years of use. Although it is difficult to decipher the specific factors contributing to the successful management in patients with AIT, Kotwal et al 67 suggested that the outcome of these patients is most likely derived from the coordinated efforts of endocrinologists, thyroid surgeons, cardiologists, anesthesiologists, and members of all of collaborating teams.…”
mentioning
confidence: 99%
“…Amiodarone is a benzofuranic, iodine-rich antiarrhythmic drug (class III) that causes thyroid dysfunction in 15 to 20% of patients (1). In each 200-mg tablet, there is 75 mg of iodine (37% of the amiodarone mass) of which approximately 10% of the iodine is released as free iodide daily.…”
Section: Discussionmentioning
confidence: 99%
“…Radioactive iodine can be used where thioamide drugs have been used initially to render an individual with AIT type 1 euthyroid, but who is unable to come off the oral agents. In more resistant cases, thyroidectomy may be an option (1,4).…”
Section: Discussionmentioning
confidence: 99%
“…Хирургическое вмешательство позволяет быстро устранить тиреотоксикоз. Такой подход считается безопасным для пациентов с тяжелыми нарушениями ритма сердца, которым невозможна отмена Ам, а быстрое восстановление эутиреоза консервативными методами недостижимо [65,66].…”
Section: лечениеunclassified